(untitled) (Circe de clásicos y modernos, 2020)
This article tries to determine the relevance of variants that are not innovations to filiate witnesses of a given work. Taking as its starting point a sugges-tive example by E. Menestò (I), it underlines the helical process leading to the construction of a stemma (II-III); it explains the purely negative relevance of genuine lessons (which allow to discard certain stemmata as in-valid) (IV); it reviews the notions of lectiones adiaphorae (equally good) y equipollentes (equally good not only in themselves but also in the wider stemma) and offers a brief conclusion (V).